Rasionalitas Tindakan Mengonsumsi dan Mengoleksi Merchandise K-pop Pada Remaja di Surabaya - Faradilla Delphina Rahma Putri; Diyah Utami (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
The Korean Wave phenomenon has increased the consumption and collection of K-pop merchandise among adolescents. This study aims to identify the characteristics of K-pop fans, analyze their motivations and objectives in consuming and collecting merchandise, describe the process of obtaining merchandise, and examine the rationality of their actions based on Max Weber's Social Action Theory. This study employed a qualitative method using the Verstehen approach. The participants were ten adolescent K-pop fans in Surabaya selected through purposive sampling. The researcher served as the main instrument, supported by interview and observation guidelines. Data were collected through in-depth interviews and observations and analyzed using the Verstehen approach through observation, interpretation, empathy, and generalization. The findings indicate that albums and photocards are the most commonly consumed and collected merchandise. Fans are mainly motivated by admiration for their idols, emotional satisfaction, support for idols, and the desire to complete their collections. Although emotional factors strongly influence purchasing decisions, participants also consider financial conditions, prices, product quality, usefulness, and resale value before making purchases. Based on Max Weber's Social Action Theory, affective action is the dominant form of action, followed by instrumental rational action, value-rational action, and traditional action. Therefore, consuming and collecting K-pop merchandise reflects not only emotional motives but also rational considerations.